2008
DOI: 10.1080/01292980802344216
|View full text |Cite
|
Sign up to set email alerts
|

Urban entrepreneurs, ICTs, and emerging theories: a new direction for development communication1

Abstract: The case is presented for reorienting the current paradigm of development communication to place greater reliance on new theoretical perspectives about the network society and to bring those theories to bear on studies of information and communication technologies (ICTs), especially mobile phones, in the relatively under-examined research setting of urban entrepreneurial activity. Support for this argument is made by reviewing the current and near-future state of information and communication technologies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Similarly, lack of knowledge on the use of ICTs to communicate information and knowledge was another challenge. This is in agreement with Levy and Banerjee (2008) who observed that majority of the fishermen live in rural areas and most of them have no idea or knowledge on how to use ICTs for accessing information. Other constraints mentioned by majority of artisanal fishermen were lack of support from the government and lack of awareness on the use of ICTs for disseminating fishery information.…”
Section: Challenges On Icts Usagesupporting
confidence: 91%
“…Similarly, lack of knowledge on the use of ICTs to communicate information and knowledge was another challenge. This is in agreement with Levy and Banerjee (2008) who observed that majority of the fishermen live in rural areas and most of them have no idea or knowledge on how to use ICTs for accessing information. Other constraints mentioned by majority of artisanal fishermen were lack of support from the government and lack of awareness on the use of ICTs for disseminating fishery information.…”
Section: Challenges On Icts Usagesupporting
confidence: 91%
“…According to a number of studies, mobile technology has had the most rapid deployment in international society of all available communication technologies (Geser 2004;Meso et al 2005;Gray 2006;Castells et al 2007;Levy and Banerjee 2008;Kreutzer 2009aKreutzer , 2009bDe Bruijn et al 2009;Ekine 2010). In 2001, 28 of 54 African countries had more mobile phones than fixed-line subscribers (Meso et al 2005: 120).…”
Section: The Digital Divide and Mobile Phone Usage Patterns In Africamentioning
confidence: 99%
“…Quite a few respondents asserted that they believed the technology could replace computers in the home, and be used for social purposes, but could not do so in a business environment: 'In the business sense computers and laptops will always be used, mobile phones are more for social purposes'. This is an interesting finding, as several of the respondents indicate that they do not believe mobile technology can take the place of computers for business purposes, such as liaising with clients or updating of resource and databases, despite research that indicates otherwise (Meso et al 2005;Levy and Banerjee 2008).…”
Section: Findings: Qualitative Sectionmentioning
confidence: 99%
“…Levy and Banerjee (2008) traced the theoretical development in development communication. Based on the works of Lerner, Rogers and Castells, they identified conceptual landmarks ranging from media and social change, the diffusion of innovation and the creation of an information society to the networked society.…”
Section: Theorymentioning
confidence: 99%